Contribution of glycerol addition and algal–bacterial cooperation to nutrients recovery: a study on the mechanisms of microalgae‐based wastewater remediation. Issue 6 (5th March 2020) - Xu, Mingyu; Zeng, Qingqing; Li, Huankai; Zhong, Yuming; Tong, Linying; Ruan, Roger; Liu, Hui
Abstract: BACKGROUND: Microalgae biotechnology is considered as a promising way to recover nutrients from centrate wastewater for value‐added biomass production, but it is rarely adopted in a real‐world application. Current study confirmed that carbon deficiency and suspended solids are two problems jeopardizing the microalgae‐based wastewater remediation. In this regard, glycerol was added into centrate wastewater as exogenous carbon source and algal–bacterial cooperation for nutrients recovery assessment. RESULTS: The results showed that glycerol addition increased the biomass yield of algae from 1.54 to 2.58 g L −1 in 5‐day culture and, at the same time, improved the removal efficiency of nitrogen and phosphorus, which were further assessed by pilot‐scale experiments. Bacterial community analysis indicated that algal–bacterial cooperation involves carbon dioxide and oxygen exchange, phosphorus absorption, and solid organics degradation, forming a complementary nexus beneficial for wastewater treatment. CONCLUSION: Glycerol is proven to be a good carbon source for microalgae growth in the centrate wastewater. Additionally, the cooperation between microalgae and bacteria plays a key role in the nutrients removal during centrate wastewater. It is expected the technology and knowledge provided by current work can further promote the industrialization of microalgae‐based wastewater remediation. © 2020 Society of Chemical Industry